Programming C# 3.0 - Liberty, Jesse; Xie, Donald (Sebastopol, CA : O'Reilly, 2008)
Explores the key concepts of C# 3.0, the features of .NET 3.5 to access and work with data, ways to use C# with the Microsoft frameworks to build applications, and how to use the .NET CLR to deploy and manage data.
"Covers Visual Studio 2008, LINQ, .NET 3.5, and more"--Cover.
Includes index.
Keywords: C# (Computer program language); Microsoft .NET Framework; C# (Computer language); Computer programming; Microsoft .NET.